1999
DOI: 10.1103/physrevlett.82.5148
|View full text |Cite|
|
Sign up to set email alerts
|

Indium Segregation and Enrichment in CoherentInxGa1xAs/GaAsQua

Abstract: Significant differences in the image features of In x Ga 12x As quantum dots (QDs) grown on (001) and vicinal (001) GaAs were seen in [001] on-zone bright-field transmission electron microscope images. Simulated images were obtained by modeling the strain field distribution of the QDs with finite element analysis and then using this model in dynamical electron diffraction contrast simulations. Comparison of the experimental images and the simulated images shows that (i) In segregation exists in the QDs and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 21 publications
2
36
1
Order By: Relevance
“…This can be investigated further with the growth of binary InAs islands which would also eliminate possible effects from indium enrichment in ternary alloys. 8,9 In conclusion, we have shown that the sizes of surface and capped InGaAs QDs differ, and that this discrepancy increases with decreasing island coverage. Differences in island coverage were obtained with simultaneous growths on different GaAs ͑100͒ vicinal surfaces and with structures deposited at growth rates varying with position.…”
mentioning
confidence: 65%
“…This can be investigated further with the growth of binary InAs islands which would also eliminate possible effects from indium enrichment in ternary alloys. 8,9 In conclusion, we have shown that the sizes of surface and capped InGaAs QDs differ, and that this discrepancy increases with decreasing island coverage. Differences in island coverage were obtained with simultaneous growths on different GaAs ͑100͒ vicinal surfaces and with structures deposited at growth rates varying with position.…”
mentioning
confidence: 65%
“…Although many investigations have concentrated on the shape and size 6,7 and evolution 8,9,10 during the QD growth, relatively less attention has been paid to the composition. 11,12,13 In the classical Stranski-Krastanow 14 ͑S-K͒ mode of coherent island formation, one material with a different lattice parameter and low interfacial energy is initially deposited on a substrate surface, layer by layer, forming a ''wetting layer''. When the wetting layer reaches a critical thickness ͓usually three to five monolayers for pure Ge on Si͑001͒, 3,15 island growth starts to partially release the mismatch strain energy between the epitaxial layer and the substrate.…”
mentioning
confidence: 99%
“…Indium segregation and enrichment of InGaAs/GaAs͑100͒ QD's has been found to result in QD's with average indium compositions 30%-45% higher than that of the deposited film. 6 Stress-induced indium enrichment of quantum dots formed from In x Ga 1Ϫx As films has been predicted to reduce the nucleation barrier for islanding, with a resultant island composition that depends critically on the island shape and fractional elastic relaxation of the island relative to the planar layer. 7 Indium enrichment effects have not been determined in InGaAs/GaAs(311)B QD's, but may well be reduced relative to ͑100͒ QD's, which would result in a higher gallium content in (311)B QD's compared to ͑100͒ QD's of similar diameter.…”
Section: Temperature-dependent Plmentioning
confidence: 99%